2020
DOI: 10.1186/s13071-020-04274-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and zoonotic potential of Enterocytozoon bieneusi, Giardia duodenalis and Cryptosporidium sp. in farmed masked palm civets (Paguma larvata) in southern China

Abstract: Background: Masked palm civets are known to play an important role in the transmission of some zoonotic pathogens. However, the distribution and zoonotic potential of Enterocytozoon bieneusi, Giardia duodenalis and Cryptosporidium spp. in these animals remain unclear. Methods: A total of 889 fecal specimens were collected in this study from farmed masked palm civets in Hainan, Guangdong, Jiangxi and Chongqing, southern China, and analyzed for these pathogens by nested PCR and DNA sequencing. Results: Altogethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
1
19
2
Order By: Relevance
“…The introgression of Group 1 sequences could have led to the broad host range and increased zoonotic potential of Group 2 E. bieneusi in China. Contradictory to the finding the Group 2 genotypes almost exclusively in ruminants elsewhere, Group 2 genotypes are increasingly reported in other animals in China, including horses, dogs, cats, rodents, nonhuman primates, and various wildlife and semi-domesticated animals [ [25] , [26] , [27] , [28] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ]. Molecular epidemiological studies have further shown that Group 2 genotypes of E. bieneusi are more likely to infect humans in China than in other regions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introgression of Group 1 sequences could have led to the broad host range and increased zoonotic potential of Group 2 E. bieneusi in China. Contradictory to the finding the Group 2 genotypes almost exclusively in ruminants elsewhere, Group 2 genotypes are increasingly reported in other animals in China, including horses, dogs, cats, rodents, nonhuman primates, and various wildlife and semi-domesticated animals [ [25] , [26] , [27] , [28] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ]. Molecular epidemiological studies have further shown that Group 2 genotypes of E. bieneusi are more likely to infect humans in China than in other regions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are more than 600 genotypes, and most genotypes can be found in both humans and animals, showing zoonotic potential ( Li et al, 2019a , b ; Zhang, 2019 ; Zhang et al, 2021 ). The three enteric eukaryotic agents can infect humans through the fecal–oral route, via direct contact with infected individuals or ingestion of contaminated water or food ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining species and genotypes ( C. occultus , C. muris , and bamboo rat genotype II) have been found in only a few animals ( Table 1 ), thus could represent native parasites of other rodents. In the latter, bamboo rat genotype is genetically similar to a genotype in found in a masked palm civet ( Yu et al, 2020 ). The intensity of oocyst shedding was higher when animals were infected with C. parvum and C. parvum -like genotype (bamboo rat genotype III) than with other Cryptosporidium spp.…”
Section: Cryptosporidium Spp In Farmed Exotic Animalsmentioning
confidence: 71%